Association between sex hormone-binding globulin (SHBG) and metabolic syndrome among men - Emmanuela Quental Callou de Sá; Francisco Carleial Feijó de Sá; Kelly Cristina Oliveira; Fausto Feres; Ieda Therezinha Nascimento Verreschi (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: Metabolic syndrome consists of a set of factors that imply increased risk of cardiovascular diseases. The objective here was to evaluate the association between sex hormone-binding globulin (SHBG), sex hormones and metabolic syndrome among men. DESIGN AND SETTING: Retrospective analysis on data from the study "Endogenous oestradiol but not testosterone is related to coronary artery disease in men", conducted in a hospital in São Paulo. METHODS: Men (aged 40-70) who underwent coronary angiography were selected. The age, weight, height, waist circumference, body mass index and prevalence of dyslipidemia, hypertension and diabetes of each patient were registered. Metabolic syndrome was defined in accordance with the criteria of the Third Report of the National Cholesterol Education Program Expert Panel on Detection, Evaluation and Treatment of High Blood Cholesterol in Adults (NCEP-ATPIII). Serum samples were collected to assess the levels of glucose, total cholesterol, HDL-cholesterol (high density lipoprotein), triglycerides, albumin, SHBG, estradiol and total testosterone (TT). The levels of LDL-cholesterol (low density lipoprotein) were calculated using Friedewald's formula and free testosterone (FT) and bioavailable testosterone (BT) using Vermeulen's formula. RESULTS: 141 patients were enrolled in the study. The prevalence of metabolic syndrome was significantly higher in the first SHBG tercile than in the second and third terciles. A statistically significant positive association between the SHBG and TT values was observed, but no such association was seen between SHBG, BT and FT. CONCLUSION: Low serum levels of SHBG are associated with higher prevalence of metabolic syndrome among male patients, but further studies are required to confirm this association.